Cost-effectiveness analysis of toripalimab plus chemotherapy as the first-line treatment in patients with advanced non-small cell lung cancer (NSCLC) without EGFR or ALK driver mutations from the Chinese perspective - Zhou, Kexun; Shu, Pei; Zheng, Hanrui; Li, Qiu (Frontiers in Pharmacology, 2023)
Objectives The results of CHOICE-01 study indicated that toripalimab (anti-PD-1 antibody) plus chemotherapy provided superior outcomes in patients with advanced non–small-cell lung cancer (NSCLC) with manageable safety profile, compared with chemotherapy alone. This study was performed to assess the cost-effectiveness of combined therapy as first-line treatment for this patient population from Chinese payer’s perspective. Materials and Methods Basic data was derived from CHOICE-01 study. Markov models were developed to simulate the process of advanced NSCLC, including progression-free survival (PFS), progression disease (PD), and death in intention-to-treat (ITT) population, as well as patients with squamous or non-squamous NSCLC. Cost was obtained from local institution, and the value of utilities were referred to previous studies. Monte Carlo simulations were performed to depict the probabilistic scatter plots of incremental cost-effectiveness ratio (ICER) and acceptability curves, aiming to address the uncertainty of model inputs. Results Compared with standard chemotherapy, toripalimab plus chemotherapy yield an ICER of 21,563 per quality adjusted life year (QALY) in ITT population. For patients with squamous NSCLC, comparing the combined therapy with chemotherapy led to an ICER of 18,369 per QALY, while the ICER was 24,754 per QALY in patients with non-squamous NSCLC. With the threshold of willingness-to-pay we set (37,653 per QALY), toripalimab plus chemotherapy dominated chemotherapy in these patient population. Conclusion For patients with advanced NSCLC, toripalimab plus chemotherapy was the optimal choice as first-line treatment, regardless of histology.